Candid Lying and Precocious Storytelling in Victorian Literature and Psychology. (1st October 2016) - Laing, Roisín
Abstract: By comparing Frances Hodgson Burnett's A Little Princess (1905) with contemporaneous psychology and canonical literature, this article suggests that children's literature complicates our understanding of nineteenth-century discourse about precocity. In much canonical literature of the Victorian period, the precocious child is an agent in a narrative of adult redemption. In Victorian child psychology, childhood storytelling was associated with lying and with moral insanity; adult stories are, implicitly, true by contrast. Both discourses thus reduce the precocious child to the role of agent in the tacit truth of adult stories; many such nineteenth-century scientific and literary studies of precocity are therefore, more essentially, studies of the adult reflected in the precocious child. A Little Princess, in contrast, is concerned with the experiences and perspective of its precocious child protagonist, Sara Crewe. Through this focus on the child herself, A Little Princess suggests that the position of the precocious child in contemporary discourse is a result of the threat she represents to the adult, and to the supposed truth of adult stories. Sara Crewe obviates the moral difference between adults' stories and children's stories, and between truth and deceit, upheld in contemporary psychology. She therefore undermines the difference between adult and child which informed debate about precocity in canonical fiction and psychology of the Victorian period. In A Little Princess, this transgression of boundaries is a productive, enabling, and even moral act.